HUBUNGAN FAKTOR INDIVIDU DAN FAKTOR OKUPASI TERHADAP KELUHAN MUSCULOSKELETAL DISORDERS PADA PENGRAJIN TENUN IKAT DI KABUPATEN KLUNGKUNG - Krismayani, Devi; Muliawan, Partha (ARCHIVE OF COMMUNITY HEALTH; Vol 8 No 1 (2021): April 2021DO - 10.24843/ACH.2021.v08.i01.p03, 2021)
ABSTRACT The complaint of Musculoskeletal Disorders (MSDs) is a complaint on the skeletal muscle felt by a person ranging from a very mild complaint to terribly ill. Weaving craftsmen is one of the risky workers that suffer from complaint of musculoskeletal disorders because the work process is done manually and continuously. The purpose of this research is to know the relationship between individual factors (age, BMI and working period) and occupational factors (work attitude and duration of work) with complaint of MSDs in weaver in Klungkung Regency. This research is an analytical study with a quantitative approach using cross-sectional design. Determination sample in this study using accidental sampling method (n=42). MSDs complaints on craftsmen are measured using Nordic Body Map (NBM). The result of this study showed that the proportion of MSDs complaints is 73,81% with the most complaints at their waist (73,81%), back (69,05%), and hip (54,76%). There is a positively correlated between tenure, work behaviour at their neck, and work behaviour at their back (p<0,05). Multivariable analysis showed that only work behaviour at their back variable had a significant relationship with the complaint of Musculoskeletal Disorders (MSDs) after the independent variables were controlled (p<0,05; OR=8,49). Keywords : Ikat Weaving craftsmen, MSDs complaints, individual and occupational factors